The impact of the coronavirus outbreak (COVID-19) on player salaries, transfer fees, and net transfer expenses in the English Premier League - Quansah, T.; Frick, B.; Lang, M.; Maguire, K. (2020)
The COVID-19 pandemic has caused significant disruption in the sports industry but is still largely unexplored. Our paper tries to shed first light on this issue by examining the consequences of the coronavirus crisis for the player labor market in the English Premier League (EPL). Using data from the EPL, we develop an empirical model to calculate the expected effect of COVID-19 on the three revenue sources (TV revenues, match revenues and commercial revenues) of EPL clubs and forecast the impact on player salaries, market values, and transfer expenses in three possible coronavirus scenarios. In the forthcoming EPL season 2020/21, we expect total club revenues to decrease by 28% (worst case), 18% (medium case), and 13% (best case). Moreover, our empirical model suggests that player salaries, market values, and transfer expenses will all decrease in the upcoming season. The magnitude of the reduction depends on the scenario and ranges from -20.4% to -9.5% for player salaries and -26.7% to -12.4% for player market values. When splitting the sample into the Big6 clubs and the remaining 14 teams, our model predicts that player salaries will decline more at the Big-6 clubs than for the other 14 teams, while the opposite is true for net transfer expenses. The study adds to the understanding of the effects of COVID-19 on sports and aims at providing new insights to sport management professionals as for the development of the football labor market.